Analisa dan Perancanagan Sistem Informasi Inventori Produk Non-BBM PT. Pertamina (Persero) - Gladly Caren Rorimpandey; Olivia Kembuan (INFORMAL: Informatics Journal, 2016)
Unit Sales VII of  PT. Pertamina (Persero) in Bitung Area is one of the Area which place for giving service for the North Sulawesi, the Gorontalo and the Middle Sulawesi (Except Palu). In addition to the fuel distributor, the company also markets products of non-fuel such as lubricants, LPG​​, Chemical Agriculture and so on. However, in the process of storage of non-fuel products, there are several problems such as the data collection process takes a long time because it is done manually which is written on the card type 50, the reporting process becomes cumbersome and often inaccurate because the product data to be reported should be included one by one in a spreadsheet. The purpose of this study is to analyze and design information systems Inventory Products Non-fuel that can help PT. Pertamina (Persero) UPMS VII Depot Bitung in controlling inventory goods and preparation of non-fuel products to improve the performance of the company. By using SDLC systems development methodologies and data modeling tools ERD and DFD Inventory Information System can then be analyzed and designed.